2021
DOI: 10.3390/ijerph18158201
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Reported Physical Fitness during Late Pregnancy with Birth Outcomes and Oxytocin Administration during Labour—The GESTAFIT Project

Abstract: We explored (a) the associations between self-reported maternal physical fitness and birth outcomes; (b) whether self-reported maternal physical fitness (PF) is related to the administration of oxytocin to induce or stimulate labour. Pregnant women from the GESTAFIT project randomized controlled trial (n = 117) participated in this prospective longitudinal study. Maternal physical fitness was assessed through the International Fitness Scale at the 34th gestational week. Maternal and neonatal birth outcomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…On the other hand, while total PA is associated in multiple studies with better obstetric and perinatal outcomes [55][56][57], WTPA has been shown in others as a detrimental element that increases the risk of complications such as severe preeclampsia [58].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while total PA is associated in multiple studies with better obstetric and perinatal outcomes [55][56][57], WTPA has been shown in others as a detrimental element that increases the risk of complications such as severe preeclampsia [58].…”
Section: Discussionmentioning
confidence: 99%